Vitamin A Cassava for Nigeria - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Paul Ilona, Country Manager, HarvestPlus Nigeria - speaks on increasing nutrient levels in crops to solve micro-nutrient related problems globally. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: https://ccafs.cgiar.org/blogs/aasw6 http://www.fara-africa.org/scienceweek/